Project EDIT: an aid to improve the academic performance of Grade 10- Emerald students in Science amidst pandemic. - Vivian Grace Perez (IJCER (International Journal of Chemistry Education Research), 2023)
The COVID-19 Pandemic has been one of the most significant disruptions in education in the Philippines. The shift to remote distance teaching meant a rapid change to alternate modes of teaching and learning. The pandemic had a silver lining as it opened doors to new ideas and technologies that could be leveraged to enhance education. Distance learning with self-learning modules is not enough to reach and teach students at Der-An Integrated School, Diffun, Quirino. As a result, different strategies and integration of technologies are being implemented to ensure that learning never stops amidst the pandemic. Thus, this study aimed to determine the academic performance of Grade 10 students in Science. A group Pretest Post-test Research design was utilized to determine the academic performance of Science among Grade 10 students as being affected by Project EDIT (Effective Delivery of Lessons by Integrating Technologies). The technologies being implemented include laptops, mobile phones, and Two-way radios. Prior to the implementation of this project, a pretest was conducted to determine the initial academic performance of the respondents just by the use of purely self-learning modules. Two weeks after the implementation of this project, a post-test was administered to test their academic performance. Employing this design on a group of 22 Grade 10- Emerald Students, the following were found: there is a significant difference in the mean scores of the respondents on their pretest and post-test, and the project EDIT had a large effect. Through the aforementioned results, it was concluded that Project EDIT is an effective tool for class discussion to improve the academic performance of students amidst the pandemic.